(untitled) - Tenenbaum, Aaron M. (Englewood Cliffs, N.J., 1990)
Contents: Introduction to data structure, The stack, Recursion, Queues and Lists, Trees, Sorting, Searching, Graphs and Their Applications, Storage Management.
Keywords: Cấu trúc dữ liệu (Khoa học máy tính),Data structures (Computer science)